Growth and survival rate of Nandus nandus (Hamilton 1822) larvae on some selected supplemental feeds in cistern - Begum, Nilufa; Pramanik, Md Mehedi Hasan; Mahmud, Yahia (Asian Journal of Medical and Biological Research, 2017)
The aim of the investigation was to determine the effect of different food on growth and survival of Nandus nandus larvae. The experiment was conducted for 20 days in twelve (12) cisterns (9× 6×2.5ft) to assess the effect of Zooplankton, Artemia, Tubifex and Brand Nursery Feed on growth and survival of N. nandus larvae in cistern condition. The growth of N. nandus larvae varied significantly (P<0.05) with live feed and artificial feed. Zooplankton treatment showed the best growth performance and Brand Nursery Feed showed the poorest. There was significant difference in final weight of larvae fed with live and artificial feed. Final weight of live feed Zooplankton was 241.79±17.25g, Artemia-210.37±20.16g, Tubifex-226.36±15.72g and Brand Nursery Feedwas195.08±15.53g respectively. Specific growth rate (%) and percentage (%) weight gain were also best in case of Zooplankton fed N. nandus larvae. Different water quality parameters were more or less same in different treatments. Asian J. Med. Biol. Res. March 2017, 3(1): 114-119